How to achieve better effect of peer support among adults with type 2 diabetes: A meta-analysis of randomized clinical trials. Issue 2 (February 2016) - Zhang, Xuxi; Yang, Shuaishuai; Sun, Kaige; Fisher, Edwin B.; Sun, Xinying
Highlights: We evaluated the general effect of peer support on glycemic control. Peer support provided by patients themselves or nonprofessionals had better effect. Peer support of Home-visit and Curriculum-combined-reinforcement had better effect. Duration of peer support with the best cost-effectiveness is >3 and ≤6 months. Abstract: Objectives: To study the effects of peer support on glycemic control and examine effects of different providers and types of support, intervention duration and effect duration.